Concrete hardening accelerator containing galvanic sludge (rus) - Stepanov S.V. (Инженерно-строительный журнал, 2012)
One of the most effective ways to reduce power inputs to the manufacture of concrete and reinforced concrete products is the use of hardening accelerator additives that reduce the time or lower the temperature of thermal processing. From economic and ecological points of view it is expedient to use the by-products and waste industry for the production of additives. In this paper we propose the use of galvanic sludge, which structure contains oxide, hydroxide and aluminum sulphate. Its use leads to an increase in the strength of cement stone in the first hours and days of hardening, as the number of Ettringite increases in the system. As galvanic sludge is a fine product, it is more effectively used in conjunction with superplasticizer, resulting in a complex chemical additive. Application of such additives enables to triple the durability of the cement stone at the age of 12 hours, and to increase in two times the concrete strength at the age of 1 day of hardening. The effectiveness of additives remains constant when changing the mobility of the mixture, that allows applying it in different ways of forming concrete products.